2011
DOI: 10.1213/ane.0b013e3181fcc504
|View full text |Cite
|
Sign up to set email alerts
|

The Wolf Is Crying in the Operating Room

Abstract: Approximately 80% of the total 8975 alarms had no therapeutic consequences. Implementation of procedure-specific settings and optimization in artifact and technical alarm detection could improve patient surveillance and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 13 publications
3
30
1
1
Order By: Relevance
“…Also this alternative analytical pathway would rest on an extensive research base of how to design and understand joint cognitive healthcare working environments (Cook and Woods, 1996;Woods, 1995;Schmid et al, 2011;Raymer et al, 2012;Raymer and Bergström, 2013;Klein et al, 2004;Hollnagel and Woods, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also this alternative analytical pathway would rest on an extensive research base of how to design and understand joint cognitive healthcare working environments (Cook and Woods, 1996;Woods, 1995;Schmid et al, 2011;Raymer et al, 2012;Raymer and Bergström, 2013;Klein et al, 2004;Hollnagel and Woods, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, false alarms vastly outnumber real events because disconnection of sensors (“asystole”), blood draws, and electrocautery are more common than cardiac arrest in most ORs 113,114. Monitoring devices can also fail from heavy use.…”
Section: Partmentioning
confidence: 99%
“…Schmid et al [19] studied perioperative alarms in a highly complex surgical setting and included 25 patients undergoing elective cardiac surgery with extracorporeal circulation. All patient monitor and anesthesia workstation alarms were digitally recorded.…”
Section: Alarm-related Problemsmentioning
confidence: 99%
“…Schmid et al found different characteristic patterns and density of alarms in 4 different intraoperative phases (beginning of surgery, start of extracorporeal circulation [ECC], end of ECC, end of surgery) [19]. …”
Section: Technical Approaches For False Alarm Reductionmentioning
confidence: 99%
See 1 more Smart Citation